2000
DOI: 10.1128/jb.182.22.6532-6535.2000
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Role of recA in Phenotypic Switching of Pseudomonas tolaasii

Abstract: Switching between the pathogenic smooth (1116S) and nonpathogenic rough (1116R) forms of Pseudomonas tolaasii occurs due to the reversible duplication of a 661-bp element within thepheN locus. Disruption of the chromosomal recAlocus of 1116S and 1116R produced strains 1116SrecAand 1116RrecA, respectively, which showed typical loss of UV resistance. Switching from the smooth to the rough form was virtually eliminated in the 1116SrecA strain, whereas the extent of switching from the rough to the smooth form was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Although this result cannot exclude the possibility that recombinational processes are involved in this phase variation, it shows that RecA and RecB are not essential for the repair of mutations in gacS and gacA of PCL1171. A similar observation was made for P. tolaasii (37), where RecA was not needed for the removal of the duplication in pheN (37).…”
Section: Vol 187 2005 Gacs and Pseudomonas Colony Phase Variation 597mentioning
confidence: 65%
“…Although this result cannot exclude the possibility that recombinational processes are involved in this phase variation, it shows that RecA and RecB are not essential for the repair of mutations in gacS and gacA of PCL1171. A similar observation was made for P. tolaasii (37), where RecA was not needed for the removal of the duplication in pheN (37).…”
Section: Vol 187 2005 Gacs and Pseudomonas Colony Phase Variation 597mentioning
confidence: 65%
“…However, the introduction of gacA gene into the F variant did not complement morphology. Although the appearance of gacA/gacS-related phenotypes among phase variants in different species of fluorescent pseudomonads (12,15,24,54) and the alteration in pyoverdin production in a P. aeruginosa sss mutant suggest that the gacA gene might be subjected to phase variation, phenotype selection is also possible. Our results, the sequencing of gacA allele in variant F showing point mutations, and the appearance of gacA mutants from plants inoculated with F113-sss2 demonstrated that during rhizosphere colonization, this gene is not subjected to phase variation, but a selection of the phenotype is occurring.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, they may have arisen through a topoisomerase I-mediated process (6). In vitro biofilm-associated acapsular phase variants with tandem sequence duplications in cps3D have also been described in the literature (33) and may arise through either recA-independent or recAdependent mechanisms, or through both types of mechanisms (27,31,32).…”
Section: Discussionmentioning
confidence: 99%